2002
DOI: 10.1002/jsfa.1251
|View full text |Cite
|
Sign up to set email alerts
|

Digestive utilisation of protein and amino acids from raw and heated lentils by growing rats

Abstract: The effect of autoclave treatment on the digestive utilisation of protein and amino acids from lentils was studied in growing rats. Twenty 3-week-old Wistar rats (mean live weight 59 AE 4.8 g) were fed two experimental diets (n = 10 rats per diet) consisting of raw lentils (Lens culinaris M, var vulgaris, cv magda-20) (diet RL) or lentils autoclaved at 120°C and 1 atm for 30 min (diet AL). An additional group of 10 animals was fed a low-protein (4%) diet and used to estimate metabolic nitrogen and amino acid e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 37 publications
3
15
0
2
Order By: Relevance
“…Glutamic, aspartic and arginine acids were found to be the major non-essential amino acids in lentil seeds protein 21.40, 13.70 and 7.60%, respectively. These results are in good agreement with the values reported by several authors (Carbonaro et al, 1997;Kavas and Nehir, 1992;Mahmoud and El-Anany, 2014;Rozan et al, 2000;Porres et al, 2002). Germination process has a positive effect on the essential amino acid contents in lentil seeds.…”
Section: Amino Acidssupporting
confidence: 93%
See 1 more Smart Citation
“…Glutamic, aspartic and arginine acids were found to be the major non-essential amino acids in lentil seeds protein 21.40, 13.70 and 7.60%, respectively. These results are in good agreement with the values reported by several authors (Carbonaro et al, 1997;Kavas and Nehir, 1992;Mahmoud and El-Anany, 2014;Rozan et al, 2000;Porres et al, 2002). Germination process has a positive effect on the essential amino acid contents in lentil seeds.…”
Section: Amino Acidssupporting
confidence: 93%
“…Sulfur-containing amino acids were the fi rst limiting amino acid, while threonine was the second limiting amino acid in raw and germinated lentil seeds. The results of the current study agree with the fi ndings of Porres et al (2002) who found that methionine + cysteine were the fi rst limiting AAs in lentil seeds. The chemical score, an index of protein quality was estimated by comparing the essential amino acid contents of raw and germinated lentil seeds with a reference amino acid pattern (FAO/WHO, 1991).…”
Section: Amino Acidssupporting
confidence: 92%
“…In sterilised seeds of the cultivar Alamo, increases were noted in the content of isoleucine, lysine, phenylalanine, total essential amino acids, arginine, serine, glycine and total non-essential amino acids; in Flaforte, there were increases in phenylalanine and glutamic acid; and in Mona, in serine and proline. According to Chau et al (1997), Khalil and Mansour (1995) and Porres et al (2002), prolonging the time and increasing the temperature of thermal processing brought about greater changes in the content of different amino acids expressed in 16 g N, depending on the analysed legume species; however, their level could also have been affected by the solubility of protein in water; possible damage to the seed coat (Ruiter, Schuurmans, & Kollöffel, 1984); or by the stronger absorbency of brine by swelling starch (Desphande & Cheryan, 1986). On the other hand, heat may also alter the amino acids residues chemically, for example dehydration of serine, deamination of glutamine and asparagine; it may also lead to the formation of new infra-or intermolecular bonds, and also heat denaturation breaks covalent disulphide bonds, liberating hydrogen sulphide (Espe & Lied, 1999).…”
Section: Amino Acid Seedsmentioning
confidence: 99%
“…The effect of processing on the antinutritional factors of rapeseed has been reported. Heat treatments were reported to remove the ANFs of CM (Mansour et al, 1993;Newkirk & Classen, 2002), soybean meal (Kaankuka, Balogun, & Tegbe, 1996;Katic, Krizic, Pliestic, & Tajana, 1996) and flaxseed meal (Madhusudhan & Singh, 1985b;Porres et al, 2002). It was found that applying the high temperature destroyed the glucosinolates and improved the canola meal flavor and palatability (Niewiadomski, 1990;Jensen, Liu, & Eggum, 1995).…”
Section: Introductionmentioning
confidence: 94%